Super size - Carey, Craig Robert; Mones, Isidre; Mones, Marc. (New York : Scholastic Inc., 2005)
Looks at huge vehicles and equipment that are used in construction, mining, transportation and other endeavors. Includes descriptions of gigantic dump trucks, ladder trucks, telehandlers, cruise ships, aerial trucks, container ships, freight trains, tankers, crawler- transporters and the International Space Station.
Keywords: Monster trucks -- Juvenile literature; Ocean liners -- Juvenile literature; Cargo ships -- Juvenile literature; Railroad trains -- Juvenile literature